A comparison of assessment tools for childcare centers in high vs. low resource settings - Huynh, Hy V.; Puffer, Eve; Ostermann, Jan; Weinhold, Andrew K.; Lopez, Meghan E.; McGovern, Melissa; Whetten, Kathryn (Frontiers in Public Health, 2024)
Studies suggest issues may arise when using childcare setting assessment tools designed for high-resource settings in low-resource settings to assess and improve the quality of care, including placing disproportionate weight on features of the childcare environment that may not be available or culturally appropriate within the low-resource context. This study compares a novel assessment tool developed in and for low-income and low-resource settings with a standardized “gold standard” tool developed for use in high-resource settings. The study included a randomized sample of 34 childcare centers in a low-resource context that provided care for approximately 918. Results suggest that the WCI-QCUALS assessment tool performed better at differentiating among childcare settings that were consolidated into the lowest rating on the ECERS-R. Further, the WCI-QCUALS was found to be a feasible, appropriate stand-alone tool for assessing the quality of childcare centers in low-resource settings. Additional refinement and validity testing in other countries and contexts will improve the understanding of how the quality of childcare across different contexts can be measured, and improved assessment of childcare quality in low-resource settings will enhance the ability to identify low-quality care that can be remedied to ensure appropriate care for vulnerable children.